Understanding fibroblast heterogeneity in the skin. Issue 2 (February 2015) - Driskell, Ryan R.; Watt, Fiona M.
Highlights: Fibroblasts are functionally heterogeneous. Heterogeneity is attributable to distinct lineages. Fibroblasts are regulated by epidermal Wnt signalling. Abstract : Fibroblasts are found in most tissues, yet they remain poorly characterised. Different fibroblast subpopulations with distinct functions have been identified in the skin. This functional heterogeneity reflects the varied fibroblast lineages that arise from a common embryonic precursor. In addition to autocrine signals, fibroblasts are highly responsive to Wnt-regulated signals from the overlying epidermis, which can act both locally, via extracellular matrix (ECM) deposition, and via secreted factors that impact the behaviour of fibroblasts in different dermal locations. These findings may explain some of the changes that occur in connective tissue during wound healing and cancer progression.